OP0294 Pro-Inflammatory FCRL4+ Memory B Cells in Joints of RA Patients; Immunoglobulin Gene Characteristics and Antigen Specificity. (9th June 2015) - Amara, K.; Yeo, L.; Sippl, N.; Clay, E.; Spengler, J.; Titcombe, P.; Filer, A.; Raza, K.; Malmstrom, V.; Scheel-Toellner, D.
Abstract : Background: We have recently identified a subset of pro-inflammatory memory B cells in RA synovial fluid and tissue, characterised by the expression of Fc receptor-like 4 (FcRL4) 1-3 . These cells produce RANKL, and express high levels of TNFa mRNA, indicating a destructive, pro-inflammatory role. Their immunophenoptype suggest that they are activated B cells; however, they show no signs of differentiation towards plasmablasts, suggesting that their functional role does not involve antibody production. Objectives: The aim of this project was to investigate the characteristics of the immunoglobulin genes expressed in FcRL4+ B cells isolated from RA synovial fluid and tissue and to determine whether their B cell receptors recognise known autoantigens. Methods: Single FcRL4-positive and -negative B cells were sorted from synovial tissue (n=2) and synovial fluid (n=5) of patients with active RA. Their Ig variable region genes were sequenced and subsequently expressed to generate recombinant monoclonal antibodies. Antigen specificities of the generated monoclonal antibodies were determined by ELISA. Results: In total, we have cloned and sequenced B cell receptors from 332 individual B-cells (171 from FcRL4+ and 160 from FcRL4- cells). Ig gene sequence analysis demonstrated that the Ig repertoire was highly diverse with no major differences in the IGH and IGK or IGL gene segment usage or IGH CDR3 features between FcRL4+ and FcRL4- memory B cells. The prevalence of mutations, suggesting somatic hypermutation and selection in germinal centres, was equivalent in the FcRL4+ and FcRL4- populations. From the sequenced clones we have generated recombinant monoclonal antibodies from both FcRL4+ (n=29) and FcRL4– B cells (n=26) and have determined their specificity for citrullinated candidate autoantigens. A similar proportion of recombinant antibodies derived from the FcRL4+ and FcRL4- B cell populations (23% and 24% respectively) reacted with citrullinated antigens (including a-enolase, fibrinogen, vimentin and histones) Conclusions: We conclude that memory B cells from both the FcRL4+ and FcRL4- populations are post-germinal centre hypermutated B cell subsets with similar Ig gene features. Their antigen specificity suggests that these functionally distinct B subpopulations both emerge from the autoantigen driven immune response in the inflamed joint. References: Yeo L, Toellner KM, Salmon M, et al. Cytokine mRNA profiling identifies B cells as a major source of RANKL in rheumatoid arthritis. Ann Rheum Dis. Nov 2011;70(11):2022-2028. Yeo L, Lom H, Juarez M, et al. Expression of FcRL4 defines a pro-inflammatory, RANKL-producing B cell subset in rheumatoid arthritis. Ann Rheum Dis. Jan 15 2014. Ehrhardt GR, Hsu JT, Gartland L, et al. Expression of the immunoregulatory molecule FcRH4 defines a distinctive tissue-based population of memory B cells. J Exp Med. Sep 19 2005;202(6):783-791. Disclosure of Interest: None declared